2016
DOI: 10.5152/iao.2015.1450
|View full text |Cite
|
Sign up to set email alerts
|

Radiological Imaging Findings of Patients with Congenital Totally Hearing Loss

Abstract: OBJECTIVE:The aim of this study was to determine and classify inner ear abnormalities in patients who had cochlear implants because of congenital sensorineural hearing loss using preoperative temporal bone computed tomography and magnetic resonance imaging. MATERIALS and METHODS:Patients in the otolaryngology department who had cochlear implants because of congenital sensorineural hearing loss between January 2011 and December 2013 were included in the study. There were 167 male and 133 female patients, a tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…In our study 74.2% and 94.6% cases revealed no ear deformity or abnormality on CT and MRI respectively. These figures correspond to a study conducted in 2015 in whichinner ear abnormalities were demonstrated to be 20% 17 . Cochlear aplasia or absence of the eighth nerve are absolute contraindicationsto cochlear implantation and puts a halt to the further process of cochlear implant if any of two is demonstrated 12 .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In our study 74.2% and 94.6% cases revealed no ear deformity or abnormality on CT and MRI respectively. These figures correspond to a study conducted in 2015 in whichinner ear abnormalities were demonstrated to be 20% 17 . Cochlear aplasia or absence of the eighth nerve are absolute contraindicationsto cochlear implantation and puts a halt to the further process of cochlear implant if any of two is demonstrated 12 .…”
Section: Discussionsupporting
confidence: 89%
“…This condition requires slight change of procedure as either short array electrodes are used or incomplete insertion of electrodes is done is dysplastic cochlea.1.2 %of patientsshowed high jugular bulb which is included in vascular anomalies. Tomura et al showed percentage of 2.4% in a study conducted in 1995 18 and 3.5% in another study conducted in 2015 17 .…”
Section: Discussionmentioning
confidence: 90%
“…It is found in approximately 25–48% of patients with unilateral hearing loss 46 . Moreover, bilateral CND is found in approximately 15.4% of patients with severe-to-profound bilateral hearing loss 7 . It has been reported that the hearing threshold and word recognition score of unilateral deafness may be related to the size of bony cochlear nerve canal, which is associated with CND 8,9 .…”
Section: Introductionmentioning
confidence: 99%
“…Abnormalities might encompass cochlear (about half of inner ear malformations) and/or labyrinthine bone structures, reflecting a developmental failure during early inner ear embryogenesis. The detection rate of common cavity deformity widely ranges between 0.7% and 26% of cochlear malformations. Such a wide incidence rate range likely reflects the differences in the study inclusion criteria, one of which might strictly consider ovoid cochlear-vestibular cysts centered by the IAC and another that might include a continuum of malformations that encompass cochlear aplasia and severe cases of incomplete partition type 1.…”
Section: Epidemiologic Studiesmentioning
confidence: 99%